COVID-19: What can we learn from shared experiences of social distancing within secure services?. (1st September 2020) - Straiton, David
COVID-19 is an infectious disease that has spread across the globe with a social, economic and psychological impact that will undoubtedly change the world in which we live. Those working in mental health services will have experienced major changes in working practices, including navigating the challenges of infection control, whilst caring for some of the most vulnerable members of our society. There have been a number of publications considering many of the practicalities of the COVID-19 challenges in mental health. However, deeper reflections of philosophical issues regarding our own shared experiences have not yet been well covered in the professional press. This commentary describes some experiences of working within a low secure forensic service at the beginning of the COVID-19 pandemic in the UK. It aims to explore some of the key themes arising from this unprecedented situation, proposing areas for reflection and shared learning within the mental health inpatient community.